1994
DOI: 10.1093/carcin/15.2.415
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk of GSTM1 null genotype is dependent on the extent of tobacco smoke exposure

Abstract: Recently, homozygous gene deletion of GSTM1, one of the Mu class glutathione S-transferase isozymes, was found to occur in approximately half of the population of various ethnic origins and has been implicated in tobacco-related carcinogenesis. In the present study we evaluated the risk of GSTM1 null genotype for lung cancer in relation to the extent of tobacco smoke exposure in 178 lung cancer patients (157 males, 21 females) and 201 healthy controls (140 males, 61 females), who were all Japanese and current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…This was observed for lung cancer where frequent smoking (Kihara et al, 1994) or low vitamin C consumption (Garcia-Closas et al, 1995) results in a higher cancer risk in the GSTM1 0 population than in the non-null population.…”
Section: Discussionmentioning
confidence: 88%
“…This was observed for lung cancer where frequent smoking (Kihara et al, 1994) or low vitamin C consumption (Garcia-Closas et al, 1995) results in a higher cancer risk in the GSTM1 0 population than in the non-null population.…”
Section: Discussionmentioning
confidence: 88%
“…This direct effect has been shown in lung cancer patients with GSTM1- (Kihara et al, 1994) and PAH-albumin adducts (Autrup et al, 1995). These effects may be due to a more gene-environ-ment interactions at high levels of exposure to PAHs when CYP1A1 will be induced and there may not be enough GST enzymes to detoxify PAH derivatives.…”
Section: Discussionmentioning
confidence: 95%
“…An association between deficient GSTM1 activity and an increased risk of adenocarcinoma of the lung among smokers would be a cofounding factor (Seidegard et al, 1990). And some studies suggested that the GSTM1 null genotype is associated with increased risk of squamous cell carcinoma of lungs which is the lung cancer most clearly related to smoking (Hirvonen et al, 1993;Kihara et al, 1994). On the other hand, other authors found a significant negative correlation between adenocarcinoma of lung and the GSTM1 null genotype and a significant positive correlation to adenocarcinoma of colon (Zhong et al, 1991;.…”
Section: Discussionmentioning
confidence: 99%